2016
DOI: 10.1002/cssc.201600140
|View full text |Cite
|
Sign up to set email alerts
|

Facile Uptake and Release of Ammonia by Nickel Halide Ammines

Abstract: Although major difficulties are experienced for hydrogen‐ storage materials to meet performance requirements for mobile applications, alternative fuel cell feedstocks such as ammonia can be stored in the solid state safely at high capacity. We herein describe the NiX2‐NH3 (X=Cl, Br, I) systems and demonstrate their exceptional suitability for NH3 storage (up to 43 wt % NH3 with desorption that begins at 400 K). The structural effects that result from the uptake of NH3 were studied by powder X‐ray diffraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The highest capacity (gravimetric density of ammonia) materials-typically hexammines-can be synthesised simply by the ambient temperature and pressure ammoniation of the respective transition metal salts. In an earlier study, we identified nickel salts as a promising group of ammonia storage materials [4]. Associated with this work, we were able to demonstrate that the reaction of ammonia with nickel nitrate hexahydrate induces ligand exchange and the growth of nickel nitrate hexammine crystals [5].…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…The highest capacity (gravimetric density of ammonia) materials-typically hexammines-can be synthesised simply by the ambient temperature and pressure ammoniation of the respective transition metal salts. In an earlier study, we identified nickel salts as a promising group of ammonia storage materials [4]. Associated with this work, we were able to demonstrate that the reaction of ammonia with nickel nitrate hexahydrate induces ligand exchange and the growth of nickel nitrate hexammine crystals [5].…”
Section: Introductionmentioning
confidence: 53%
“…Unlike these copper and platinum compounds, which achieve three-dimensional connectivity through hydrogen bonds, Ni(NH3)2(NO3)2 is connected in all three dimensions via bridging nitrate anions. 4 ] octahedra connected through four bridging nitrate anions per metal centre (and hence, each individual nitrate ligand bridges two metal centres, Figure 4). The nitrate ligands are located in the equatorial positions with the ammonia ligands trans-to one-another in the axial positions.…”
Section: Crystal Structure Of Ni(nh3)2(no3)2mentioning
confidence: 99%
See 3 more Smart Citations